Mutations in the ribosome biogenesis factor gene LTV1 are linked to LIPHAK syndrome, a novel poikiloderma-like disorder. Issue 12 (6th January 2022) - Han, Ji Hoon; Ryan, Gavin; Guy, Alyson; Liu, Lu; Quinodoz, Mathieu; Helbling, Ingrid; Lai-Cheong, Joey E; ,; Barwell, Julian; Folcher, Marc; McGrath, John A; Moss, Celia; et al.
Abstract: In the framework of the UK 100 000 Genomes Project, we investigated the genetic origin of a previously undescribed recessive dermatological condition, which we named LIPHAK (LTV1-associated Inflammatory Poikiloderma with Hair abnormalities and Acral Keratoses), in four affected individuals from two UK families of Pakistani and Indian origins, respectively. Our analysis showed that only one gene, LTV1, carried rare biallelic variants that were shared in all affected individuals, and specifically they bore the NM_032860.5:c.503A > G, p.(Asn168Ser) change, found homozygously in all of them. In addition, high-resolution homozygosity mapping revealed the presence of a small 652-kb stretch on chromosome 6, encompassing LTV1, that was haploidentical and common to all affected individuals. The c.503A > G variant was predicted by in silico tools to affect the correct splicing of LTV1 's exon 5. Minigene-driven splicing assays in HEK293T cells and in a skin sample from one of the patients confirmed that this variant was indeed responsible for the creation of a new donor splice site, resulting in aberrant splicing and in a premature termination codon in exon 6 of this gene. LTV1 encodes one of the ribosome biogenesis factors that promote the assembly of the small (40S) ribosomal subunit. In yeast, defects in LTV1 alter the export of nascent ribosomal subunits to the cytoplasm; however, the role of this gene in human pathology is unknown to date. Our data suggest that LIPHAK could be a previously unrecognized ribosomopathy.